American Extraterritorial Legislation: The Data Gathering behind the Sanctions. Issue 166 (1st March 2021) - Laïdi, Ali
Abstract: Since the early 2000s, the United States' different administrations of justice have been prosecuting foreign companies suspected of violating US laws on bribery of foreign public officials and of failing to respect embargoes and economic sanctions. Even if these violations take place outside US borders, the American prosecution authorities (including the Department of Justice, the Securities and Exchange Commission and the Office of Foreign Assets Control) consider themselves legitimate to intervene. European multinationals have been particularly sanctioned. For instance, in 2014, fines reached up to 9 billion dollars for the French bank BNP, which was accused of using dollars in its transactions with certain countries sanctioned by the US (mainly Iran, Cuba and Sudan). Punishing companies and hitting them in the wallet are not the only objectives of the American administration. The United States takes advantage of legal procedures against foreign companies to collect millions of bytes of data, sometimes including sensitive information on them as well as on their partners and markets. Facing this legal offensive, Europe is still struggling to provide responses to protect its companies.